Insect pathogens: molecular approaches and techniques - Stock, S. P.; Boemare, N.; Boemare, N.; Glazer, I.; Glazer, I.; Stock, S. P.; Vandenberg, J.; Vandenberg, J. (Wallingford :CABI, 2009)
This book attempts to bring together a broad array of molecular techniques and approaches currently used in insect pathology. It is divided into four parts: (i) identification and diagnostics; (ii) evolutionary relationships and genetics; (iii) host-pathogen interactions; and (iv) genomics and genetic engineering. Sixteen chapters have been written by leading researchers in the field which provide comprehensive and up-to-date information on each part.
Keywords: YY300 - Genetics and Molecular Genetics (Wild Animals), (New March 2000); YY700 - Pathogens, Parasites and Infectious Diseases (Wild Animals), (New March 2000); ZZ360 - Molecular Biology and Molecular Genetics, (Discontinued March 2000, Reinstated and Revised June 2002); ZZ900 - Techniques and Methodology